Analisis Tata Kelola E-Government Pelayanan Administrasi Menggunakan Framawork COBIT 5 - Ilham Wahyuni (Jurnal Informatika Ekonomi Bisnis, 2022)
Information Technology (IT) and Information Systems have a very important role for the Department of Population and Civil Registration of Tanah Datar Regency (DUKCAPIL). DUKCAPIL is a government service in population administration matters. To find out that DUKCAPIL's performance is in accordance with the plan, it is necessary to analyze E-Geverment governance. This study aims to determine the level of capability (capability level) and system improvement by monitoring, reviewing and measuring in the application of IT at DUKCAPIL Tanah Datar. IT governance analysis uses the COBIT 5 framework with 5 domains, namely EDM (Evaluating, Direction, and Monitoring), APO (Align, Plan, Organise), BAI (Build, Acquire, and Implement), DSS (Deliver, Service and Support) , and MEA. The method of data collection in this study was a literature study (review of IT application and literature study) question and answer in interviews and filling out questionnaires, then an analysis was carried out to determine the level of ability and gaps in the application of IT. The results of the EDM domain at level 2, APO at level 1, BAI at level 1, DSS at level 1, and MEA (Monitoring, Evaluate, and Asses) at level 2. The level of capability obtained from the analysis results is the capability level of DUKCAPIL Tanah Datar when viewed from the EDM04 Ensure Resource Optimization process and MEA01 Monitor, Evaluate and Assess Performance and Conformance are at level 2 Managed Process. This shows that the process has been recorded, measured and in accordance with the objectives. The APO07 Manage Human Resources, BAI09 Manage Assets and DSS01 Manage Operations processes are at level 1 Performed Process, which means that the process has been applied to DUKCAPIL Tanah Datar.